المعيقات والصعوبات التي يواجهها الطلبة بالتعليم الإلكتروني في الجامعات الفلسطينية - أبو معيلق، كرم عطوة; عواد، مريم عبدالكريم طلال; عدوان، نسرين فضل (مركز البحث وتطوير الموارد البشرية - رماح, 2020)
الصعوبات والمعيقات التي تواجه الطلبة أثناء التعليم الإلكتروني، وتكون مجتمع الدراسة من طلبة الجامعات الفلسطينية، واختيرت عينة الدراسة بطريقة عشوائية لتطبيق عليهم استبانة الدراسة، فاستجاب منهم (500) طالب وطالبة. توصلت الدراسة إلى عدة نتائج جاء أهمها أن الصعوبات التي يواجهها الطلبة في التعليم الإلكتروني جاءت مرتبة كالتالي، المجال الثالث: صعوبات تتعلق بالمنهاج الجامعي قد حصل على المرتبة الأولى بوزن نسبي قدره (75.8% وحصل المجال الثاني: صعوبات تتعلق بالطلبة على المرتبة الثانية بوزن نسبي قدره (72.38%) وحصل المجال الأول: صعوبات تتعلق بالإدارة الجامعية بوزن نسبي قدره (71.7%) أما الدرجة الكلية للاستبانة ككل حصلت على وزن نسبي (73.3%). كما بينت النتائج أنه لا يوجد فروق بين متغيرات الدراسة تعزى لمتغير الجنس والتخصص والجامعة والمستوى الجامعي.
The study aimed to identify the obstacles and difficulties that students face in e-teaching from Palestinian universities and to identify whether there are differences related to statistical study between the basic study variables due to gender, specialization, university and academic level. To achieve the aims of the study, the descriptive analytical method was used, and the study tool is a questionnaire to measure the difficulties and obstacles facing students during the electronic education, the study society is from Palestinian university students, and the study sample was chosen in a random way for them to identify the study, so they responded (500) students. The study reached several results, the most important of which was that the difficulties faced by students in e-learning were ranked as follows, the third field: difficulties related to the university curriculum has obtained the first rank with a relative weight of (75.8%) and the second field: difficulties related to students on the second rank with a relative weight of (72.38%), and the first field: difficulties related to university administration with a relative weight of (71.7%). As for the overall degree of the questionnaire as a whole, it obtained a relative weight (3.73%). The results also showed that there are no differences between the study variables due to the gender, specialization, university, and university level.
Keywords: التعليم الإلكتروني -- صعوبات التعلم -- طلبة الجامعات -- مؤسسات التعليم العالي -- فلسطين